2001
DOI: 10.1183/09031936.01.00009301
|View full text |Cite
|
Sign up to set email alerts
|

The sleep apnoea/hypopnoea syndrome depresses waking vagal tone independent of sympathetic activation

Abstract: The modest daytime hypertension and sympathetic upregulation associated with the sleep apnoea/hypopnoea syndrome (SAHS), does not explain the relatively large increased risk of cardiac morbidity and mortality in the SAHS patients population. Therefore, efferent vagal and sympathetic activity was evaluated during wakefulness in SAHS subjects and matched healthy controls, in order to determine if vagal downregulation may play a role in the aetiology of cardiac disease in the SAHS.The awake autonomic nervous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 47 publications
0
42
0
1
Order By: Relevance
“…Subjects with SDB, who are subjected to repetitive episodes of nocturnal intermittent hypoxia and transient arousal from sleep, have been shown in numerous studies to display abnormalities in autonomic function, as represented by reduced HRV or autonomic stress tests, [17][18][19][20][41][42][43] as well blunted baroreflex sensitivity. [44][45][46][47][48] However, there have been studies that have reported negative findings; for example, in a study involving PSGs from 61 male obstructive sleep apnea subjects and 43 controls, Coughlin and associates 10 did not find any significant association between baroreflex sensitivity and RDI.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with SDB, who are subjected to repetitive episodes of nocturnal intermittent hypoxia and transient arousal from sleep, have been shown in numerous studies to display abnormalities in autonomic function, as represented by reduced HRV or autonomic stress tests, [17][18][19][20][41][42][43] as well blunted baroreflex sensitivity. [44][45][46][47][48] However, there have been studies that have reported negative findings; for example, in a study involving PSGs from 61 male obstructive sleep apnea subjects and 43 controls, Coughlin and associates 10 did not find any significant association between baroreflex sensitivity and RDI.…”
Section: Discussionmentioning
confidence: 99%
“…The SCN is entrained to the environmental light-dark cycle by specialized photoreceptors within the eye (Foster and Hankins 2007;Lockley and Foster 2012). The SCN in turn co-ordinates the activity of the entire circadian network and most 24-hour behavioural, metabolic and physiological rhythms including alertness and performance, hormones, core body temperature, metabolism and the different rhythms in key organs such as the lungs, liver and heart (Hilton et al 2001;Hastings, Reddy, and Maywood 2003). If this entrainment pathway is disrupted at any point, then the biological clocks in different tissues can become uncoupled, resulting in a state of internal desynchrony of the 24-hour oscillator network (Foster et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of the sympathetic efferent arm of the arterial chemoreflex arc was suggested by prevention of the blood pressure response after pharmacological sympathetic blockade or carotid body deafferentiation (16 -19, 50). On the other hand, withdrawal of parasympathetic activity could also contribute to the alteration of sympathovagal balance observed in obstructive sleep apnea, as shown by power spectrum analysis of heart rate variability (26,35,55).…”
mentioning
confidence: 99%
“…Involvement of the sympathetic efferent arm of the arterial chemoreflex arc was suggested by prevention of the blood pressure response after pharmacological sympathetic blockade or carotid body deafferentiation (16 -19, 50). On the other hand, withdrawal of parasympathetic activity could also contribute to the alteration of sympathovagal balance observed in obstructive sleep apnea, as shown by power spectrum analysis of heart rate variability (26,35,55).Perinatal susceptibility to hypoxia is characterized by the developmental window of vulnerability. Thus the presence of normoxia during the first 7-10 days of postnatal life in rats is critical for development of chemoreceptor sensitivity (1,2,7,15,29).…”
mentioning
confidence: 99%